Pengaruh Green Behaviour dan Green Inovation terhadap Corporate Sustainability Performance - Lifiya Kholifatunnisa; Bayu Kurniawan; Noni Setyorini (Green Economics Review, 2025)
This study aims to examine the influence of green behavior and green innovation on corporate sustainability performance, with a focus on KOPERSEMAR Group. The research employs a quantitative approach. The population consists of all employees working at the KOPERSEMAR Group office in Semarang. The sampling technique used is purposive sampling, resulting in a total sample of 172 respondents. This study applies Multiple Linear Regression Analysis using SPSS Version 26 to analyze the data. The findings indicate that green behavior does not have a significant impact on corporate sustainability performance. However, green innovation has a positive and significant effect on corporate sustainability performance. These results suggest that while environmentally friendly behaviors among employees may not directly enhance corporate sustainability performance, the implementation of innovative green practices within the company plays a crucial role in achieving sustainability goals. The findings contribute to the growing body of literature on sustainable corporate practices by highlighting the importance of green innovation in organizational performance. Companies seeking to enhance their sustainability performance should focus on fostering green innovation through technological advancements, process improvements, and sustainable product development. Future research could explore the moderating or mediating factors that might strengthen the relationship between green behavior and corporate sustainability performance. Additionally, expanding the study to different industries or incorporating qualitative insights could provide a more comprehensive understanding of the dynamics between green practices and corporate sustainability.